Pathophysiology and Treatment of Fibromyalgia Syndrome - Stratz, Thomas; Schneider, Marion; Joos, Thomas O.; Hsu, Hsin-Yun; Muller, Wolfgang (Current Rheumatology Reviews, 2007)
Fibromyalgia syndrome is not a diagnosis in itself, but merely represents a set of classification criteria. It is possible to distinguish between different subgroups. Such a distinction can be made on the basis of psychopathological, clinical and laboratory tests. One subgroup reveals elevated level of different cytokines. The treatment of primary fibromyalgia can be optimized by taking these subgroups into consideration since one group responds better to 5-HT3 receptor antagonists, whereas another benefits more from antidepressants and a third group from psychotherapy. In socalled secondary fibromyalgia, 5-HT3 receptor antagonists may be used in the attempt to manage pain that might still persist after treatment of the primary disease.
Keywords: psychotherapy